The Moderating role of Information Technology in the relationship between the Re-Engineering of Administrative Processes and The Institutional Performance of the Yemeni General Electricity Corporation (2018-2022) - Al-Muhrami, Munif Ahmed Saif; Alawi, Nahg AbdulMajid (Journal of Economic, Administrative and Legal Sciences, 2023)
The institutional performance of the Yemeni General Electricity Corporation in the production of electric power is still facing severe criticism. Therefore, the corporation sought to re-engineer its operations due to the fact that the re-engineering of administrative processes helps to get out of the routine, the narrow view of work, the lack of inclusiveness, the quick solutions to work problems, and other traditional administrative systems and methods using modern technologies. Therefore, the current study aimed to examine the impact of re-engineering of administrative processes on the institutional performance of the Yemeni General Electricity Corporation in with the use of information technology as a moderating variable. In order to achieve these objectives, a questionnaire was designed and distributed to all general managers, their deputies, administration managers, their deputies, and department heads in the General Electricity Corporation, Aden branch, which totaled 419 directors and deputy directors, and through the Cronbach alpha scale, the stability of all study variables was confirmed. Structural equations modeling was used to test the hypotheses of the study. The study concluded that there is an effect of the variable of using information technology as a moderator in the relationship between re-engineering of administrative processes and all dimensions of institutional performance. The study recommended the need for the General Electricity Corporation to apply the entrance to process re-engineering for its role in improving the improvement of institutional performance in its various dimensions.